Succession of mycotoxigenic fungi in relation to storage and mycotoxin production on stored paddy (Oryza sativa) - and S.M. REDDY, KIRAN SAINI*, M. SUREKHA (Indian Phytopathology, 2013)
Influence of storage structures on the incidence of mycotoxigenic fungi on paddy during one year (November-2010 to October-2011) storage in pot, polythene bag, tin and gunny bag was analysed both qualitatively and quantitatively. The incidence of fungi increased with the advance of storage. Some of the fungi which were present during initial storage disappeared at later stage and vice versa. In general Aspergillus flavus, A. terreus, A. niger and some species of Fusarium and Penicillium were recorded throughout the storage period. Many mycotoxigenic fungi exhibited high potential of elaborating respective mycotoxins. Mycotoxins like aflatoxins, ochratoxin-A, citrinin, trichothecenes and zearalenone were elaborated by respective fungi with significant levels of toxigenic potential.